TYPE, CAUSE, AND EFFECT OF BULLYING IN A GIRL LIKE HER MOVIE - Lia Nurmalia; Baiatun Nisa; Mutiara Safitri; Retno Dwigustini (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
Bullying is a serious problem which must be solved and eradicated. School is the most place of bullying action, since students come from different social background are gathered in a long time. This research investigates the case of bullying in A Girl Like Her movie. The investigations are limited into three main problems. They are type, cause, and effect of bullying. This research uses descriptive qualitatuve approach as the method analysis. The results show there are four types of bullying found in the movie, they are verbal 52.4%, physical 19%, cyber 14.3%, and relation 14.3%. The most type of bullying is verbal. Later, the cause of bullying which found in this movie is only social factor, since the intimidator has a parental problem in her family. Lastly, the effect of bullying to the victim are stress, emotional disorder, and behaviour disorder for the serious problem by trying to kill her self by drinking over dose medicine.